2010
DOI: 10.1387/ijdb.082829pb
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial responses to embryonic signals in the primate

Abstract: The delicate interaction between an embryo and the uterus to initiate implantation and maintain pregnancy is one of the most elegant and fascinating interactions in human biology. Understanding the molecular events of embryo-maternal interaction is of interest to reproductive biologists, clinicians and couples affected by infertility. We have established the baboon as the non-human primate model for studying embryo implantation. Infusion of chorionic gonadotropin (CG), the major embryonic signal of primates, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 102 publications
0
53
0
Order By: Relevance
“…The investigators proved that these responses were inhibited after treatment with progesterone receptor antagonist. It is possible that hCG intrauterine injection before ET, as described in our study, produced the various changes in the endometrium described in the experiments done by Licht et al and Banerjee and Fazleabas (9,21).…”
Section: Discussionmentioning
confidence: 56%
“…The investigators proved that these responses were inhibited after treatment with progesterone receptor antagonist. It is possible that hCG intrauterine injection before ET, as described in our study, produced the various changes in the endometrium described in the experiments done by Licht et al and Banerjee and Fazleabas (9,21).…”
Section: Discussionmentioning
confidence: 56%
“…Wallace et al [13] demonstrated improved pregnancy rates after an intramuscular injection of hCG at ET in cows. In a study by Banerjee and Fazleabas [14], intrauterine injection of hCG in baboons induced a favorable uterine environment for embryo implantation. Although hCG has been commercially available for a long time, a few human trials have addressed the value of hCG injection in ET.…”
Section: Discussionmentioning
confidence: 99%
“…Intrauterine injection of hCG has been associated with significant pro-implantation changes of the endometrium in primates [14]. Moreover, in a recent study it has been shown that intrauterine injection of hCG before ET improves implantation and pregnancy rates [15].…”
Section: Introductionmentioning
confidence: 99%
“…The signalling pathways controlling plaque formation and decidualization in baboons have been the object of close scrutiny [34]. Decidual cells occur also in the vervet monkey (Chlorocebus aethiops) [35].…”
Section: Old World Monkeysmentioning
confidence: 99%